2021
DOI: 10.1021/acsami.1c03328
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stretchable PU Ionogels with Self-Healing Capability for a Flexible Thermoelectric Generator

Abstract: With the development of thermoelectric (TE) generator, the flexible, stretchable, self-healable, and wearable TE devices have aroused great interest. Therefore, we designed a self-healable and stretchable polyurethane (PU) ionogel, composed of polyurethane main chains with double bonds in the side, cross-linkers (BDB) and nonconjugated ionic liquids (EMIM:DCA). The PU ionogels with 30 wt % ILs have a high mechanical stretchability (300%), good tensile strength (1.61 MPa), and suitable Young’s modulus (0.79 MPa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 41 publications
0
58
0
Order By: Relevance
“…34 Xu et al investigated ionogels with self-healable and stretchable polyurethane (PU) as the gelator. 44 The ionogels can exhibit a ZT i of 0.99 ± 0.3 at a relative humidity of 70% and a mechanical stretchability of up to 300%. However, ILs can have problems like high cost and toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…34 Xu et al investigated ionogels with self-healable and stretchable polyurethane (PU) as the gelator. 44 The ionogels can exhibit a ZT i of 0.99 ± 0.3 at a relative humidity of 70% and a mechanical stretchability of up to 300%. However, ILs can have problems like high cost and toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Over the duration of utilization of PUs, cracks often develop from the impact, scratch, and radiation that may lead to catastrophic security problems and cut the service life of PUs. Consequently, endowing PUs with versatile properties such as self‐healing ability suggests huge potential for new‐generation PUs 20–24 . In the past decade, intrinsic healing materials with the unique flexible properties of shape memory and self‐healing have drawn great attention among researchers, which are mainly based on dynamic covalently bonded crosslinking 25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, endowing PUs with versatile properties such as self-healing ability suggests huge potential for new-generation PUs. [20][21][22][23][24] In the past decade, intrinsic healing materials with the unique flexible properties of shape memory and self-healing have drawn great attention among researchers, which are mainly based on dynamic covalently bonded crosslinking. 25,26 However, there are only a small number of studies about self-healing vegetable oil-based polymers.…”
mentioning
confidence: 99%
“…Additionally, they have no gas emission, no vibration, and a long lifespan . Advances in material engineering have shown that silk fabric-based, , paper-based, , paint-based, , and self-healing , flexible TEGs (f-TEG) can be developed.…”
Section: Introductionmentioning
confidence: 99%